Watershed Development in India : An Approach Evolving through Experience - Symle, Jim (World Bank, Washington, DC, 2014)
This report analyses the experiences and lessons from three World Bank-Supported watershed development projects in the Indian states of Karnataka, Himachal Pradesh, and Uttarakhand.5 The primary reason for the analysis was to guide the development and execution of new watershed programs in India, including new Bank-supported state-level operations in Uttarakhand and Karnataka, and a proposed national project now under preparation. Accordingly, it was important to deepen the knowledge base about large-scale, community-led watershed development in order to share that knowledge with key stakeholders both inside and outside of the World Bank. Another important reason was the immediate and growing concern over water resources and their management in India and the question of how well watershed development programs internalize these concerns. A third impetus was the nexus between rural poverty and rainfed agriculture and the important role that watershed development programs are to fulfill in the development of sustainable rural livelihoods.